STUDI PENGELOLAAN KOMITMEN KERJA GURU SEBAGAI WUJUD INTEGRASI DALAM PENCAPAIAN OPTIMALISASI KINERJA PADA MADRASAH - Handriadi Handriadi (Indonesian Journal of Basic Education, 2019)
It is a requirement for educational institutions including madrasah (islamic educational institution) to have good and solid performance appraisal and professional development programs for their employees. Performance appraisal is intended for both faculty members and non teaching staff, while professional development is only emphasized for faculty members with a permanent employment status. The author seeks to explore the issue of the effectiveness of the educational institution in this case madrasah in its effort on staffing optimization. Like other aspects, staffing is influenced by organizational dynamics. Specifically, this study focuses on the dynamics of managing employees’ security for both faculty members and non teaching staffs as well as remuneration and career development opportunities